AgNOR counts in conjunctival malignant melanoma lack prognostic value. Issue 10 (October 1992) - Paridaens, A D; Seregard, S; Minassian, D; Hungerford, J L; McCartney, A C
Abstract : Using a silver staining technique, argyrophilic nucleolar organiser region-associated proteins (AgNORs) have been studied in routinely processed paraffin sections of 46 invasive malignant melanomas (MM) of the conjunctiva. The aim of this retrospective study was to assess the value of the AgNOR method as a prognostic indicator for this neoplasm. The 46 cases were divided into two groups: (A) 14 cases of MM that metastasised and caused death of the patient within 5 years of (histological) diagnosis, and (B) 32 cases of MM that did not metastasise and in which patients survived beyond 5 years. The mean of the AgNOR counts per nucleus was 7.03 (95% CI: 5.81-8.24) in group A, and 7.15 (95% CI: 6.53-7.77) in group B. A comparison using a multifactor analysis of variance (ANOVA) model, which corrected for possible confounding effect of tumour thickness, site, and cell type showed no significant difference in AgNOR counts between groups A and B (p = 0.8). Analysis by the Cox proportional hazards regression model showed that survival was not influenced significantly by the mean AgNOR number (hazard ratio: 0.92). Whereas the AgNOR technique may be used to distinguish benign from malignant melanocytic lesions of the conjunctiva, we conclude it has no value in predicting the outcome for patients with conjunctival MM.